Esthetics in Orthodontics: interest points, reference points and discrepancy points - Câmara,Carlos Alexandre (2012)
It is fundamental for orthodontists and all professionals related with facial, oral and dental esthetics to know how the individuals observe dentofacial structures. Thus, it will be the purpose of this Orthodontic Insight to present and describe the Interest, Reference and Discrepancy. Points With the knowledge and perception of these points it will be easier for orthodontists to create a convergent canal of communication with their patients.